Correction: An assessment of factors for the cruise port of call selection: The modified fuzzy Analytic Hierarchy Process. - Thang Quyet Nguyen; Quynh Manh Doan; Lan Thi Tuyet Ngo (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0297293.].